A narrative review on the effect of economic downturns on the nursing labour market: implications for policy and planning - Alameddine Mohamad; Baumann Andrea; Laporte Audrey; Deber Raisa (BMC, 2012)
Abstract Economic downturns and recession lead to budget cuts and service reductions in the healthcare sector which often precipitate layoffs and hiring freezes. Nurses, being the largest professional group in healthcare, are strongly affected by cost reductions. Economic downturns destabilize the nursing labour market with potential negative outcomes, including serious shortages, extending beyond the recessionary period. The objectives of this manuscript are to provide an overview of the potential short- and long-run impact of economic downturns on the supply and demand of nurses, and present healthcare decision makers with a framework to enhance their ability to strategically manage their human resources through economic cycles. A narrative review of the literature on the effects of economic downturns on the nursing labour market in developed countries was carried out with a special focus on studies offering a longitudinal examination of labour force trends. Analysis indicates that economic downturns limit the ability of public payers and institutions to finance their existing health workforce. As salaried healthcare workers, nurses are especially susceptible to institutional budget cuts. In the short run, economic downturns may temporarily reduce the demand for and increase the supply of nurses, thereby influencing nursing wages and turnover rates. These effects may destabilise the nursing labour market in the long run. After economic downturns, the market would quickly display the pre-recessionary trends and there may be serious demand-supply imbalances resulting in severe shortages. Potential long-term effects of recession on the nursing labour market may include a downsized active workforce, difficulty in retaining younger nurses, a decreased supply of nurses and workforce casualisation. Lack of understanding of labour market dynamics and trends might mislead policy makers into making misinformed workforce downsizing decisions that are often difficult and expensive to reverse. In the aftermath of an economic downturn, the costs of attracting nurses back often outweigh the short term cost savings. Effective management should support the nursing workforce by creating attractive and stable work environments to retain nurses at a manageable cost.